Evaluation of a stand-alone mobile mindfulness app in people experiencing infertility: the protocol for an exploratory randomised controlled trial (MoMiFer-RCT). Issue 2 (2nd February 2022) - Boedt, Tessy; Willaert, Nele; Lie Fong, Sharon; Dancet, Eline; Spiessens, Carl; Raes, Filip; Matthys, Christophe; Van der Gucht, Katleen
Abstract : Introduction: Infertility and its treatment bring a considerable emotional burden. Increasing evidence demonstrates the effectiveness of smartphone-delivered mindfulness apps for reducing symptoms of emotional distress in both clinical and non-clinical populations. Evidence on this topic in women, men and couples experiencing infertility is currently under-represented. The aim of the MoMiFer study is, therefore, to investigate the efficacy of a stand-alone mobile mindfulness app on symptoms of emotional distress and fertility-related quality of life in people experiencing infertility. Methods and analysis: This study is an exploratory randomised controlled trial (RCT) with open enrollment. The primary outcomes are symptoms of emotional distress and fertility-related quality of life. Secondary outcomes are mindfulness skills, repetitive negative thinking, self-compassion, user-rated quality of the stand-alone mobile mindfulness app and use of the app. Experience sampling method and standardised self-report questionnaires are combined within a repeated measures design to measure the effects of the stand-alone mobile mindfulness app on the primary and secondary outcomes, apart from the use of the app. The latter will be evaluated through app tracking. People, including women, men and couples, experiencing infertility (n=60) will be randomised to an intervention group receiving the stand-alone mobile mindfulness app for 3 months or a wait-list control group. The app follows the format and content of Mindfulness-Based Stress Reduction. Data will be collected at baseline, at 1.5 months and 3 months after randomisation. Analysis will be according to intention to treat and based on general linear modelling and multilevel mixed-effects modelling. Ethics and dissemination: This study received approval from the Medical Ethical Committee of the Leuven University Hospital (Belgium). The findings of this exploratory RCT will be disseminated through presentations at public lectures, scientific institutions and meetings, and through peer-reviewed scientific articles. Trial registration number: NCT04143828 .